2007
DOI: 10.2754/avb200776020209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fungicide Euparen Multi (Tolylfluanid) on Development of Preimplantation Embryos in Mouse

Abstract: The effect of the fungicide Euparen Multi (containing 50% tolylfluanid) on the development of mouse preimplantation embryos was evaluated. Euparen Multi was daily administered per os to female mice (ICR strain) at four different doses of 118, 294, 588 and 1177 mg/kg b.m., beginning on day 1 of pregnancy. Embryos obtained on day 4 of pregnancy were stained by morphological triple staining (Hoechst 33342, propidium iodide, Calcein AM), and the number of nuclei, blastocyst formation, distribution of embryos accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Essential oils (EOs) can be extracted from fresh plant flowers or leaves and widely consumed as aroma additives in food, cosmetics, and pharmaceuticals. Thyme (Thymus vulgaris) is widely cultivated as herbal medicine, spice, and tea and is considered one of the well-known plants of Lamiaceae family and (Domaracký et al, 2007). Thyme possesses different beneficial effects, including bronchopulmonary disorders, sedative, antispasmodic, gastroenteric, anthelmintic, antimicrobial, carminative, diaphoretic, and antioxidant activities (Rustaiyan et al, 2000, Miura et al, 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Essential oils (EOs) can be extracted from fresh plant flowers or leaves and widely consumed as aroma additives in food, cosmetics, and pharmaceuticals. Thyme (Thymus vulgaris) is widely cultivated as herbal medicine, spice, and tea and is considered one of the well-known plants of Lamiaceae family and (Domaracký et al, 2007). Thyme possesses different beneficial effects, including bronchopulmonary disorders, sedative, antispasmodic, gastroenteric, anthelmintic, antimicrobial, carminative, diaphoretic, and antioxidant activities (Rustaiyan et al, 2000, Miura et al, 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Cloves show antiseptic, antibacterial, antifungal and antiviral properties . It is a popular remedy for dental disorders, respiratory disorders, headaches and sore throats in regular medicines of Australia and Asian countries . Besides its antimicrobial, antifungal and antiviral properties, clove displays cytotoxic, anesthetic and anti‐inflammatory properties .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple in vitro exposures of mouse thymocytes to pesticide were examined by Olgun et al (2004) . As regards tolylfluanid formulation (with 50% active agent), Domaracky et al (2007) reported cell death in mouse preimplantation embryos at relatively low doses. Nevertheless, the incidence of cell death has been mostly reported as necrosis.…”
Section: Discussionmentioning
confidence: 99%